Effect of nitrogen concentration on growth, lipid production and fatty acid profiles of the marine diatom Phaeodactylum tricornutum - Yodsuwan, Natthawut; Sawayama, Shigeki; Sirisansaneeyakul, Sarote (Agriculture and Natural Resources, 2017)
The marine diatom, Phaeodactylum tricornutum had a high lipid content accumulation under photoautotrophically nitrogen-deficient cultivation. The lipid content (YP/X; 53.04 ± 3.26%) was highest with a specific rate of lipid production (qP; 1.50 ± 0.12 x 10-3 mg/mg h), attained at the minimized specific growth rate (µ; 0.87 ± 0.13 x 10-2/h) after 504 h of cultivation. When the specific growth rate (µ; 2.47 ± 0.02 x 10-2/h) was maximized in nitrogen-sufficient culture (32.09 mg/L NaNO3), the specific rate of lipid production (qP; 0.42 ± 0.19 x 10-3 mg/mg h) was lowered. In this work, the nitrogen concentration with fixed phosphorus concentration was used to monitor the lipid accumulation, as the lower nitrogen concentration favored a higher lipid content percentage, compared with a higher nitrogen concentration. Under nitrogen-deficient conditions, P. tricornutum produced a large amount of saturated fatty acids, mainly as palmitic acid (C16:0), while palmitoleic acid (C16:1c) was found to be the sole unsaturated fatty acid. On the other hand, eicosapentaenoic acid (C20:5ω3c) was produced in large amounts when there was sufficient nitrogen. Since the biodiesel was qualified based on the fatty acid methyl ester composition, the oil from algae cultured under nitrogen-deficient conditions were considered to meet the biodiesel standard. Thus, P. tricornutum optimally cultivated under nitrogendeficient conditions can accumulate a high oil content, which demonstrates its potential as a biodiesel feedstock.